2019
DOI: 10.1007/s10551-019-04159-y
|View full text |Cite
|
Sign up to set email alerts
|

Ayn Rand’s Objectivist Ethics Applied to Video Game Business

Abstract: This article analyzes the business ethics of digital games, using Ayn Rand's philosophy of Objectivism. It identifies different types of monetization options as virtuous or nonvirtuous, based on Rand's views on rational self-interest. It divides the options into ethical Mover and unethical Looter designs, presents those logics in relation to an illustrative case example, Zynga, and then discusses a view on the role of players in relation to game monetization designs. Through our analysis of monetization option… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 42 publications
(37 reference statements)
1
20
0
1
Order By: Relevance
“…Moreover, other ways to monetize are by offering in-game items that enhance the gaming experience or give advantages to the players; these are known as virtual goods. (Harviainen et al, 2019). Virtual goods have become the main monetization method in F2P games (Flunger et al, 2017).…”
Section: Free-to-playmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, other ways to monetize are by offering in-game items that enhance the gaming experience or give advantages to the players; these are known as virtual goods. (Harviainen et al, 2019). Virtual goods have become the main monetization method in F2P games (Flunger et al, 2017).…”
Section: Free-to-playmentioning
confidence: 99%
“…However, the authors point out that the game creator does not necessarily have the same interest in the games as the players. Furthermore, it has been observed that not all developers may have the user's best interest in mind (Harviainen et al, 2019). Additionally, developers can have different perceptions of what they consider ethical game development.…”
Section: Ethics and Dark Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the issues of social justice that have sparked global protests have encouraged organizations to reflect on their societal role. While technology in ITT has been championed as emancipatory for individuals, organizations, and institutions, ITT researchers have paid less attention to the unethical use of technology by enterprises (such as dark patterns) (Harviainen, Paavilainen, and Koskinen 2019) or its role in facilitating discriminatory practices (Ahuja and Lyons 2019). Reflexive, critical ITT research may begin to explore and address the interconnected nature of social, digital, and economic inequalities in Tourism.…”
Section: Broaden and Open Boundaries Of Ittmentioning
confidence: 99%
“…media platform Facebook (Harviainen et al, 2019). Time and (market) information are intrinsically connected.…”
mentioning
confidence: 99%